Crystallization of waxes in sunflowerseed oil: effects of an inhibitor - Petruccelli, Silvana (1991)
The mechanism of action of a commercial inhibitor on the crystallization of waxes present in sunflowerseed oil was analyzed. The results showed the inhibitor favored nucleation, leading to a decrease in the amount of waxes available for the growth of the crystals already formed. The inhibitor decreased the crystal size, increased the number of crystals and possibly caused slower crystallization of waxes.